Induksi Kalus dari Hipokotil Alfalfa (medicago sativa l.) secara in vitro dengan Penambahan Benzyl Amino Purine (BAP) dan Î±-Naphtalene Acetic Acid (NAA) - Hayati, Surya Kurnia; Nurchayati, Yulita -; Setiari, Nintya - (Bioma : Berkala Ilmiah Biologi, 2010)
Alfalfa (Medicago sativa L.) is useful plant for treatment some diseases such as: cancer, diabetes, lupus, andhepatitis. Propagation of this plant in Indonesia face a problem which has no embryo. One method to propagate thisplant is by tissue culture or micropropagation. Callus induction is first step in micropropagation to produce calluswhich will be regenerated to become planlet. The aims of this research are to induce callogenesis from hipocotyl ofalfalfa with addition Benzyl Amino Purine (BAP) and Î± Naphtalene Acetic Acid (NAA), and to determine the propercombination of BAP and NAA to produce the optimal callus. The experiment has been conducted by using 12combination of BAP and NAA with Completely Randomized Design (CRD) in 4x3 factorial pattern by 5 replicates.Data were analyzed by ANOVA 95% Degrees of Freedom (DF). If there was significance result, it was followed byDMRT analyzed at 95 % DF. The result showed that combination of BAP and NAA was able to induce callogenesisfrom hipocotyl of alfalfa. The optimal callus was obtained in combination of BAP 0 ppm and NAA 2 ppm.